Isolation of Circulating Fetal Trophoblasts Using Inertial Microfluidics for Noninvasive Prenatal Testing. Issue 7 (14th June 2018) - Winter, Marnie; Hardy, Tristan; Rezaei, Meysam; Nguyen, Vy; Zander‐Fox, Deirdre; Ebrahimi Warkiani, Majid; Thierry, Benjamin
Abstract: While noninvasive prenatal testing based on cell‐free fetal DNA has recently revolutionized the field of aneuploidy screening in pregnancy, it remains limited to aneuploidy and microdeletion screening, and is unable to reliably detect single gene disorders. A number of recent studies have demonstrated the potential of circulating trophoblastic cells in providing cell‐based noninvasive diagnosis with sequencing or array‐based assays. However, considering the extreme rarity of these cells in blood, efficient, high‐throughput, and clinically applicable enrichment technologies are yet to be developed. This study demonstrates for the first time the utility of inertial microfluidics for efficient isolation of trophoblastic cells from maternal peripheral blood. Under optimal operating conditions, high‐recovery yields (79%) are obtained using a trophoblastic cell‐line, which is subsequently confirmed with analysis of maternal blood. Feasibility of obtaining a diagnosis from cells isolated from a maternal sample is demonstrated in a case of confirmed fetal trisomy 21 in which six fetal cells are found in a 7 mL blood sample using fluorescence in situ hybridization. Finally, it is demonstrated that trophoblastic cells isolated using inertial microfluidics could be picked and subjected to a clinically validated sequencing assay, paving the way for further validation of this technology and larger clinical studies. Abstract : The separation of fetal cells from maternal circulation using an inertial microfluidic device is demonstrated . The isolation of fetal cells from maternal blood offers a noninvasive source of the whole fetal genome, however, these cells are extremely rare requiring extremely efficient isolation technologies to allow genetic analysis. Inertial microfluidics offers a cheap and quick alternative to enrich these precious cells.